The prevalence of malposition third molar with traumatic ulcer - Tun Abdul Majid, Tun Shafiqah; Astuti, Ida Ayu; Dewi, Tenny Setiani (Padjadjaran Journal of Dentistry, 2013)
Introduction: Malposition third molar is a condition when the third molar is erupted but in an abnormal position and relation to maxilla and mandible. Due to a frequent mechanical abrasion between the third molar and oral mucosa, a traumatic ulcer resulted. Hence, this research aims to determine the prevalence of traumatic ulcer in regards to a malposed third molar in Oral and Maxillofacial Surgery Department, Rumah Sakit Hasan Sadikin in a periodic of August 2008 to August 2011.Methods: The samples taken were all medical records which stated the coveted diagnosis which satisfied the variables of the age, gender and malposed third molar. The method of this research was descriptive retrospective study by using secondary data. Results: This research ratiocinates that the prevalence of malposition third molar with traumatic ulcers is 0.012% with tooth 18 caused most traumatic ulcer. Females predominant this condition and it is common in the third decade of age. Conclusion: Derived from the outcomes of this research, it can be concluded that the prevalence of malposition third molar with traumatic ulcer in Oral and Maxillofacial Surgery Department of Rumah Sakit Hasan Sadikin from August 2008 to August 2011 is 0.012%.